INTERNATIONAL BIODIVERSITY DAY: USM RECEIVES RESEARCH GRANT FROM MOHAMED HANIFF R&D TRUST FUND - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 22 May 2017 – Universiti Sains Malaysia (USM) School of Biological Sciences welcomed and celebrated the International Biodiversity Day 2017 by organising a ceremony to present the Mohamed Haniff Award to recipients who have excelled in the field of Biology.